Literature Review: Gagal Ginjal Akut Akibat Nefrotoksisitas Gentamisin - Akbar, Dafa Rafiqi; Yonata, Ade; Ratna, Maya Ganda; Darwis, Iswandi (CV. Jasa Sukses Abadi, 2024)
Acute kidney failure or Acute Kidney Injury (AKI) is a sudden decline in kidney function that is often caused by various factors such as sepsis, ischemia, and nephrotoxicity. One of the significant causes of nephrotoxicity is gentamicin, an aminoglycoside antibiotic commonly used to treat Gram-negative bacterial infections. Although effective, gentamicin has nephrotoxic side effects, especially at high doses or long-term use, which can cause damage to the renal tubular epithelium and trigger AKI. This literature review aims to describe and study more deeply the relationship between gentamicin consumption and the incidence of acute kidney failure. Gentamicin works by inhibiting bacterial protein synthesis on the 30S ribosome. Still, its mechanism of action also has the potential to cause nephrotoxicity through drug accumulation in kidney cells, impaired mitochondrial function, increased production of reactive oxygen species (ROS), and mesangial contractions that reduce the glomerular filtration rate. Signs of gentamicin nephrotoxicity include increased serum creatinine levels, blood urea nitrogen, albuminuria, and decreased glomerular filtration rate, accompanied by structural damage such as tubular necrosis and edema in the proximal tubular epithelium. Previous studies have shown that high doses of gentamicin can increase the number of necrotic cells in the kidney and cause renal fibrosis in test animals. In humans, the incidence of gentamicin-induced nephrotoxicity has been reported to reach 10-25% of therapeutic use, with an estimated incidence of AKI of around 15% of total AKI cases. The importance of proper monitoring and management for patients using gentamicin to reduce the risk of nephrotoxicity. Prevention strategies include monitoring kidney function, dose adjustment, adequate hydration, and considering various alternative antibiotic therapies for patients at high risk of nephrotoxicity.